PENGARUH PASANGAN MEMILIKI PASANGAN SEKS LAIN TERHADAP KEJADIAN INFEKSI HIV PADA IBU RUMAH TANGGA DI RSUPH. ADAM MALIK MEDAN TAHUN 2017 - Aprilita Sitepu (STIKes Santa Elisabeth Medan, 2018)
HIV infection and AIDS are the global public health problem. Having another sex partner may increase the risk of HIV infection. Goals : This study aimed to determine the effect of having another sex partner on the incidence of HIV infection in couples in Medan. Method: This was an analytic observational study with a case-control design. The study was conducted at RSUP H Adam Malik Medan, North Sumatera, from November to December 2017. A sample of 80 housewives was selected for this study by fixed disease sampling consisting of 40 HIV infected housewives and 40 HIV uninfected housewives. The dependent variable was HIV infection. The independent variable was having another sex partner. Results: The results of multivariate analysis demonstrated that husband’s occupation (OR = 6.223), having another sexual partner (OR = 6.823) Conclusion: Couples who have another sexual partner have an increased risk of HIV infection.